Detection and antibiotic susceptibility profiles of Listeria monocytogenes in wildlife and water samples in Kubah National Park, Sarawak, Malaysia - Lesley Maurice, Bilung; Velnetti, Linang; Fazira, A.A; Kasing, Apun; Samuel, Lihan; Micky, Vincent; Awang Ahmad Sallehin, Awang Husaini (Elsevier B.V., 2016)
This study was conducted to detect the presence of Listeria monocytogenes (L. monocytogenes) and screen for its antibiotic susceptibility characteristic from wildlife and water samples at Kubah National Park, Sarawak, Malaysia. Samples collected were incubated and streaked on selective medium PALCAM agar to confirm the presence of Listeria spp. before they were further tested using molecular analysis. Specific Polymerase Chain Reaction (PCR) assay were performed to target specific virulence gene, haemolysin gene, hlyA to further distinguish the presence of this pathogenic bacteria in the samples. Overall, out of the 30 samples tested, 10 samples were confirmed as to contain L. monocytogenes strains and selected to subsequent antibiotic susceptibility test. Susceptibility patterns to 10 antibiotics were investigated among the L. monocytogenes strains. All strains were uniformly resistant to tetracycline and erythromycin. On the other hand, all strains were sensitive to gentamycin and tobramycin. The multiple antibiotic resistance shown by the strains in this study indicate the potential health hazard associated with the possible transmission between wildlife and water to its surrounding environment especially visitors and workers of Kubah National Park, Sarawak, Malaysia.